2017
DOI: 10.1080/13504851.2017.1361000
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up approach for forecasting GDP in a data-rich environment

Abstract: In an increasingly data-rich environment, the use of factor models for forecasting purposes has gained prominence in the literature and among practitioners. In this article, we extend the work of Dias, Pinheiro and Rua (2015) by assessing the forecasting behaviour of factor models to predict several GDP components and investigate the performance of a bottomup approach to forecast Portuguese GDP growth. We find supporting evidence of the usefulness of factor models and noteworthy forecasting gains when conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The bottom-up approach is used in micro-level studies where IO and CGE models cannot be easily applied, for instance in the case of assessing economic and employment impacts at the local level (Cooper et al, 2016). Bottom-up approach has been used in a wide array of disciplines to estimate economic impacts, including the transport sector in Austria (Pfurtscheller and Genovese, 2018), the energy sector in Germany (J€ ager et al, 2016), macroeconomics (Dias et al, 2018) and in the infrastructure sector (Ojha et al, 2020). Bottom-up models are more suitable for assessing socio-economic interactions in regional areas, where aggregated national-level economic data as a fundamental requirement in top-down models may not be relevant (Gajanayake et al, 2020) and have been used where economy-wide sectoral information is not available (Wiesenthal et al, 2012).…”
Section: Economic Impacts Of Maintenance Projectsmentioning
confidence: 99%
“…The bottom-up approach is used in micro-level studies where IO and CGE models cannot be easily applied, for instance in the case of assessing economic and employment impacts at the local level (Cooper et al, 2016). Bottom-up approach has been used in a wide array of disciplines to estimate economic impacts, including the transport sector in Austria (Pfurtscheller and Genovese, 2018), the energy sector in Germany (J€ ager et al, 2016), macroeconomics (Dias et al, 2018) and in the infrastructure sector (Ojha et al, 2020). Bottom-up models are more suitable for assessing socio-economic interactions in regional areas, where aggregated national-level economic data as a fundamental requirement in top-down models may not be relevant (Gajanayake et al, 2020) and have been used where economy-wide sectoral information is not available (Wiesenthal et al, 2012).…”
Section: Economic Impacts Of Maintenance Projectsmentioning
confidence: 99%
“…The most commonly used measure of the economy is GDP. Forecasting GDP is subject of concern for [Dias 2017]. The estimation for forecasting manner of the factor models with aim to prognosticate some GDP integrants is pursued as well as the efficiency of a bottom-up approach to appraise the GDP growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chan & Song (2018) indicated significant changes in the expectations, uncertainty about U.S. inflation during the Great Recession period. Dias, Pinheiro, & Rua (2018) found that factor models employing a bottom-approach for GDP is useful. Chang (2018) showed that Greenbooks (Board of Governors of the Federal Reserve System staff's forecasts) are more likely to under-predict real GDP growth with one quarter ahead forecasts.…”
Section: Literature Reviewmentioning
confidence: 99%